Development of an Outcome-Based Education (OBE) Approach in Conservation Biology Lectures to Increase Student Awareness and Conservation Efforts in the Campus Environment - Evi Apriana; Djufri; Abdullah; Nurlena Andalia (Postgraduate, University of Mataram, 2025)
This study aims to examine the application of the Outcome-Based Education (OBE) approach in Conservation Biology lectures and its impact on improving students' knowledge, practical skills, and attitudes towards conservation issues in the campus environment. This study uses a quantitative method with an experimental design, where data is collected through pre-test and post-test questionnaires, field observations, interviews, and evaluation of conservation projects carried out by students. The results showed a significant increase in students' knowledge of conservation, with the average post-test score increasing by 30%. Students also demonstrate improved practical skills in designing and implementing conservation projects, such as greening and waste management on campus. In addition, the implementation of OBE has succeeded in fostering a more caring attitude towards environmental conservation, with 75% of students showing a stronger commitment to conservation issues after attending OBE-based lectures. Student involvement in conservation activities on campus has also increased, with 70% of students actively participating in various conservation programs. However, this study also finds challenges related to limited resources and time in the implementation of larger conservation projects. Overall, this study indicates that the OBE approach can be an effective method in improving students' knowledge, skills, and attitudes towards conservation, and can strengthen environmental conservation efforts on campus.